2022
DOI: 10.3390/medicina58030332
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Prediction of Adverse Pregnancy Outcomes—Identifying Pregnancies at Risk from as Early as 11–13 Weeks

Abstract: There is consistent evidence that many of the pregnancy complications that occur late in the second and third trimester can be predicted from an integrated 11–13 weeks visit, where a maternal and fetal assessment are comprehensively performed. The traditional aims of the 11–13 weeks visit have been: establishing fetal viability, chorionicity and dating of the pregnancy, and performing the combined screening test for common chromosomal abnormalities. Recent studies have shown that the first trimester provides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Notably, ultrasound markers indicative of PASD and serum diagnostic markers, such as human chorionic gonadotropin, can manifest during the first trimester, enabling assessment and prediction of PASD severity in the first and second trimesters [ 12–14 ]. Early intervention can enhance pregnancy outcomes [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ultrasound markers indicative of PASD and serum diagnostic markers, such as human chorionic gonadotropin, can manifest during the first trimester, enabling assessment and prediction of PASD severity in the first and second trimesters [ 12–14 ]. Early intervention can enhance pregnancy outcomes [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…First-trimester screening for chromosomal anomalies is a milestone in pregnancy monitoring. The fact that screening with a combination of fetal ultrasound, maternal serum free-beta-human chorionic gonadotropin (β-hCG) and pregnancy-associated plasma protein-A (PAPP-A) can identify 90% of fetuses with trisomy 21 and other major chromosomal abnormalities with a false-positive rate of 5% [1] has drawn doctors' and researchers' attention to the possibility of screening for other pregnancy-related conditions. Scientists worldwide have concentrated on finding the first-trimester serum markers that predict other pregnancy complications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that certain maternal conditions may be predicted in the first trimester. Screening a combination of maternal factors and measuring mean arterial pressure, uterine pulsatility index, and serum placental growth factor may predict 90% of early preeclampsia cases, before 32 weeks, and 75% of preterm preeclampsia cases, before 37 weeks, with a 10% false-positive rate [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Варто зазначити, що саме плацентарне ложе є джерелом великої кількості біологічно актив-них речовин, які визначають перебіг гестації [10]. Тому на сьогодні до прогностичних моделей, які дають змогу встановити ризик ускладнень і визначити доцільність проведення профілактичних заходів, окрім різноманітних анамнестичних факторів, належать і лабораторні та інструментальні індикатори функції плаценти [4,14].…”
unclassified